Process Optimization and Flavor Substance Analysis of Probiotic Fermented Apple Juice - Xiaomin WU; Fang WANG; Yingyin GAO; Xiaobo WEI; Haitian FANG; Huiyan LIU (Shipin gongye ke-ji)
To develop a probiotic fermented apple juice that was nutritious and rich in fruit aroma. A blend of high-acid and fresh-eating apples in a 1:1 ratio was used as the raw material. Lactobacillus plantarum and Streptococcus thermophilus were employed for the fermentation process, which was optimized for best results. Gas chromatography-ion mobility spectrometry (GC-IMS) and electronic nose were employed to analyze and compared the aroma components of the fermented apple juice. Results indicated that the optimal fermentation conditions were determined as follows: 27 h of fermentation time, a fermentation temperature of 30.0 ℃, and an initial sugar content of 15.0ºBx. Under these conditions, the fermented apple juice exhibited a viable cell count of 7.2×108 CFU/mL and received a sensory score of 92.13 points. Compared to the unfermented apple juice, the fermented counterpart exhibited a significant increase in polyphenol and flavonoid content (P<0.05), while the levels of reducing sugars and lactic acid decreased significantly (P<0.05). A total of 35 volatile components were identified through GC-IMS analysis, including 6 esters, 11 aldehydes and ketones, 6 acids, 3 alcohols, 3 pyrazines, and 6 other compounds. Eleven of these components were common to both fermented and unfermented apple juices, including ethyl 2-methylbutanoate, 3,7-dimethyl-2-methylen-6-octenal, 2-heptanone, 2-cyclohexen-1-one, methyl isobutyl ketone, 3-hexanone, L(-)-carvone, pentanoic acid, 2,3-dimethyl-5-ethyl pyrazine, ethylene glycol ethyl ether, and 2,2,4,6,6-pentamethylheptane. The fermented apple juice exhibited higher levels of esters, aldehydes and ketones, and other aroma compounds compared to the unfermented counterpart (P<0.05), contributing to its enhanced floral and fruity aroma profile. Electronic nose analysis demonstrated higher response values for the fermented apple juice across all sensors compared to the unfermented counterpart, indicating that probiotics could increase the content of aromatic volatile flavor substances in apple juice.